Parasitoids of Agrilus spp. in Europe: Anticipating the arrival of Agrilus planipennis - Marc Kenis; Michael Eisenring; Martin M. Gossner; M. Lukas Seehausen (Biological Control)
The emerald ash borer (EAB), Agrilus planipennis, is a woodboring beetle native to East Asia. It is highly invasive in North America, where it causes large-scale dieback of American ash species, Fraxinus spp. EAB is also invasive in Western Russia and Ukraine, and it continues to spread towards Central and Western Europe where all three native ash species are susceptible. Biological control approaches offer sustainable solutions to control invasive pests. In North America, four Asian parasitoid species that have coevolved with EAB have been introduced to control the pest. In Europe, many species of the genus Agrilus occur, and it is likely that at least some of their parasitoids will adopt EAB as a host as it spreads across the continent. However, parasitoids of Agrilus spp., are very poorly known in Europe because of the difficulty of studying the parasitoid complex of these solitary wood boring insects. In this review, we provide a literature overview of studies and records of European parasitoids of Agrilus spp. to provide a basis for future studies on the emerging parasitoid complex of EAB in Europe. Parasitoid records were found for 24 European species of Agrilus. Sixty-four parasitoid species were recorded, mostly larval parasitoids. However, it is likely that several of them are erroneous host-parasitoid associations or misidentifications, and the biology of most species and their role in the population dynamics of their hosts has been poorly studied. It is recommended to conduct pre-emptive studies on these parasitoids and their suitability as potential biological control organisms with EAB.